Evaluation of the Effect of Latanoprostene Bunod Ophthalmic Solution, 0.024% in Lowering Intraocular Pressure over 24 h in Healthy Japanese Subjects. Issue 11 (November 2015) - Araie, Makoto; Sforzolini, Baldo; Vittitow, Jason; Weinreb, Robert
Abstract Introduction Latanoprostene bunod is a novel nitric oxide (NO)-donating prostaglandin F2α receptor agonist in clinical development for the reduction of intraocular pressure (IOP) in patients with open-angle glaucoma or ocular hypertension. We evaluated the effect of latanoprostene bunod 0.024% instilled once daily (QD) on lowering IOP over a 24-h period in healthy Japanese subjects following 14 days of treatment. Methods This was a single-arm, single-center, open-label clinical study of 24 healthy Japanese male volunteers. A baseline IOP profile was established in both eyes in the sitting position at 8 PM, 10 PM, 12 AM, 2 AM, 4 AM, 8 AM, 10 AM, 12 PM, and 4 PM using a Goldmann applanation tonometer. Subjects subsequently instilled latanoprostene bunod 0.024% QD at 8 PM for 14 days in both eyes. The absolute and change from baseline in sitting IOP was assessed on day 14. Results The mean (SD) age of the subjects was 26.8 (6.3) years, and mean (SD) baseline IOP was 13.6 (1.3) mmHg in the study eye. Latanoprostene bunod 0.024% instilled QD for 14 days reduced IOP at all the evaluated time points (P  < 0.001) with a mean (SD) 24-h reduction of 3.6 (0.8) mmHg or 27% from the baseline in the study eye. Peak and trough IOP lowering occurred at 8 AM and 8 PM (12 and 24 h following instillation) with a mean reduction of 4.2 (1.8) mmHg, or 30%, and 2.8 (2.2) mmHg, or 20%, respectively. Punctate keratitis and ocular hyperemia, both mild in severity, were the most common adverse events. Conclusion Latanoprostene bunod ophthalmic solution 0.024%, dosed QD for 14 days, significantly lowered mean IOP in healthy Japanese subjects during the entire 24-h period. Studies of latanoprostene bunod in patients diagnosed with normal tension glaucoma are warranted. Trial Registration Clinicaltrials.gov identifier NCT01895985. Funding Bausch & Lomb, Inc.